Increased exposure to pesticides and colon cancer: Early evidence in Brazil. (October 2018) - Martin, Francis L.; Martinez, Edson Z.; Stopper, Helga; Garcia, Sergio Britto; Uyemura, Sergio Akira; Kannen, Vinicius
Abstract: Environmental factors may increase colon cancer (CC) risk. It has been suggested that pesticides could play a significant role in the etiology of this malignancy. As agriculture is one of the mainstays of the Brazilian economy, this country has become the largest pesticides consumer worldwide. The CC burden is also increasing in Brazil. Herein, we examined data from the Brazilian Federal Government to determine whether CC mortality and pesticide consumption may be associated. Database of the Ministry of Health provided CC mortality data in Brazil, while pesticide usage was accessed at the website of Brazilian Institute of Environment and Renewable Natural Resources. The CC mortality in the Brazilian states was calculated as standard mortality rates (SMR). All Bayesian analysis was performed using a Markov chain Monte Carlo method in WinBUGS software. We observed that CC mortality has exhibited a steady increase for more than a decade, which correlated with the amount of sold pesticides in the country. Both observations are concentrated in the Southern and the Southeast regions of Brazil. Although ecological studies like ours have methodological limitations, the current dataset suggests the possibility that pesticide exposure may be a risk factor for CC. It warrants further investigation. Graphical abstract: Image 1 Highlights: Human exposure to xenobiotics occurs worldwide, largely. Pesticides may promote cancer risk. Brazil is the world major pesticides consumer. Colon cancer (CC) mortality is steadily increasing in Brazil. We found CC mortality and pesticide levels may be correlated events in Brazil.